2006
DOI: 10.1097/01.mbp.0000209080.24870.2d
|View full text |Cite
|
Sign up to set email alerts
|

Office blood pressure measurements overestimate blood pressure control in renal transplant patients

Abstract: Using the 24-h blood pressure as a standard, home blood pressure was superior to office blood pressure in estimating blood pressure control in renal transplant patients. Nocturnal hypertension, however, was observed frequently, adding important clinical information about blood pressure control in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…This may be due to the fact that patients were motivated as renal transplant recipients to assess their blood pressure with an extensive explanation of the positive impact both by doctors and the nurses. Stenehjem et al have already showed that home BP was superior to office BP in estimating BP control in renal transplant patients with deteriorating graft function [12]. It can also be inferred from previous studies and the present results that the predictive power of home blood pressure is largely attributable to the fact that it has multiple measurements [17].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This may be due to the fact that patients were motivated as renal transplant recipients to assess their blood pressure with an extensive explanation of the positive impact both by doctors and the nurses. Stenehjem et al have already showed that home BP was superior to office BP in estimating BP control in renal transplant patients with deteriorating graft function [12]. It can also be inferred from previous studies and the present results that the predictive power of home blood pressure is largely attributable to the fact that it has multiple measurements [17].…”
Section: Discussionsupporting
confidence: 62%
“…To clarify the level of agreement among these different blood pressure measures, a recent study compared and showed that under rigorously standardized conditions, clinic and home BP could be used as an alternative to awake ABP [11]. Even though some data exist regarding ambulatory BP monitoring in RTR, there is only few data available concerning home BP monitoring in this specific population [12]. …”
Section: Introductionmentioning
confidence: 99%
“…With transplantation, some studies suggest that dipping can be restored [57] whereas others have reported a high prevalence of non-dipping [54;58;59]. Whereas successful kidney transplantation may restore kidney function to normal, more often these patients continue to have impaired kidney function and hypertension [60].…”
Section: Diseases Associated With Impaired Circadian Bp Rhythmsmentioning
confidence: 99%
“…In a study of 36 kidney transplant recipients, all patients had either proteinuria or impaired GFR and 95% were non-dippers [61]. In another study of 49 kidney transplant recipients where all patients had either proteinuria or impaired GFR and 82% were non-dippers [58]. In a longitudinal cohort of kidney transplant recipients, GFR and age were independent correlates of non-dipping [62]Other reasons could be the use of corticosteroids which can cause endothelial dysfunction and the use of calcineurin inhibitors that can cause both endothelial dysfunction and sympathetic activation.…”
Section: Diseases Associated With Impaired Circadian Bp Rhythmsmentioning
confidence: 99%
“…Usually, the diagnosis of arterial hypertension is set using measurements performed at the physician's office, recordings traditionally called office blood pressure (BP). How reliable is office assessed blood pressure in chronic kidney disease (CKD) patients and kidney transplant (KTx) recipients is yet to be determined, as it was shown before that office BP tends to overestimate blood pressure control in renal transplantation [3]. On the other hand, ambulatory blood pressure monitoring (ABPM) seems to offer a more reliable view over arterial hypertension both in CKD and KTx patients [4][5] and also a prognostic superiority [6].…”
Section: Introductionmentioning
confidence: 99%